Detection of Free Toxin B in the Stool of Asymptomatic Clostridioides difficile Carriers by the Cell Cytotoxicity Neutralization Assay - Schweitzer, Lorne (Open Forum Infect Dis, 2021)
Cell cytotoxicity neutralization assay (CCNA) is considered to be a gold standard to diagnose Clostridioides difficile infections. We performed CCNA on 77 consecutive admission screening rectal swabs from asymptomatic toxigenic C. difficile carriers. Thirty-nine percent of specimens from asymptomatic carriers were positive. Thus, CCNA specificity may be lower than previously thought.